Morphology of Posterior Malleolus Fractures Associated with Tibial Shaft Fractures. Issue 4 (November 2022) - Myatt, Darren; Mason, Lyndon W.; Stringer, Howard; Fischer, Benjamin
Category: Trauma; Ankle Introduction/Purpose: Diaphyseal tibial fractures account for approximately 1.9% of all adult fractures. A recent registry review in Finland found an annual incidence of 15.6 in males and 11.5 per 100, 000 person-years in women. There are several studies which have demonstrated a high proportion of diaphyseal tibial fractures have ipsilateral occult posterior malleolus fractures, this ranges from 22-92.3%. Recent work by Hendrickx et al has highlighted distal third and spiral tibial shaft fracture patterns as independent predictors of occult posterior malleolus fracture. We hypothesize that this rotational element will be highlighted in the Mason & Molloy Classification of occult posterior malleolus fractures seen in tibial shaft fractures. Methods: Objectives Our primary outcome in this study was to identify any extension of tibial fractures to the posterior malleolus and describe its morphology. Study Design & Methods A retrospective review of a prospectively collected database was performed at Liverpool University Hospitals NHS Foundation Trust between 1/1/2013 and 9/11/2020. The inclusion criteria were patients over the age of 16, with a diaphyseal tibial fracture and who underwent a CT of the affected lower limb. The Mason and Molloy posterior malleolus fracture classification system was used to describe the morphology of the fracture Results: 764 diaphyseal tibial fractures were analysed, of these 300 had a CT and could be included. There were 127 intra- articular fractures. A total of 83 (27.7%) cases were classifiable using the Mason and Molloy classification. There were 8 type 1 (9.6%), 43 type 2 (51.8%), 5 type 2B (6.0%) and 27 type 3 (32.5%). The majority of the posterior malleolar fractures (n=75, 90.4%) were undisplaced pre-surgical intervention. The majority of PM fractures occurred in type 42A1 (65 of 142 tibia fractures) and 42B1 (11 of 16). Conclusion: The majority of the PM fractures associated with tibial fractures occur as a consequence of a rotational mechanism. Unlike, the PM fractures of the ankle, the majority of PM fractures associated with tibia fractures are undisplaced. We theorise that unlike the force transmission in ankle fractures where the rotational force is in the axial plane in a distal-proximal direction, in the PM fractures related to fractures of the tibia, the rotational force in the axial plane progresses from proximal-distal. Therefore, the force transmission which exits posteriorly, finally dissipates the force and thus unlikely to displace.